Case Report: The huge esophageal displacement: a case of dramatic esophageal interfraction motion during neoadjuvant chemotherapy and immunotherapy - Liang, Renba; Jin, Jing; Zhang, Jianghu; Liang, Jun (Frontiers in Immunology, 2025)
BackgroundThe average movement of esophagus is about 0.15 to 0.4 cm radially and 0.3 to 0.9 cm in the superior-inferior during radiotherapy. Little study has reported giant shift of esophagus during neoadjuvant chemotherapy and immunotherapy.Case presentationHere we presented a case of a 72-year-old male patient diagnosed with advanced lower thoracic esophageal squamous cell cancer, clinical T2N2M1, stage IVB (pulmonary metastasis). The esophagus moved about 4.2 cm radially from the right to the left of the aorta after 2 cycles of chemotherapy and immunotherapy.ConclusionAll in all, we treated a patient with advanced lower thoracic esophageal squamous cell cancer that occurred a dramatic radial escape of about 4.2 cm after 2 cycles of chemotherapy and immunotherapy.